Supramolecular surface adhesion mediated by azobenzene polymer brushes. Issue 9 (21st December 2015) - Roling, Oliver; Stricker, Lucas; Voskuhl, Jens; Lamping, Sebastian; Ravoo, Bart Jan
Abstract : Surface immobilised polymer brushes containing azobenzenes were prepared using microcontact chemistry and surface-initiated atom transfer radical polymerisation. Two surfaces bearing brushes can be glued together in the presence of a β-cyclodextrin polymer. Abstract : Surface immobilised polymer brushes containing azobenzene units were prepared using a combination of microcontact chemistry and surface-initiated atom transfer radical polymerisation (SI-ATRP). These brushes were investigated using AFM, XPS and UV/vis spectroscopy. It was shown that two surfaces bearing azobenzene brushes can be glued together in the presence of a β-cyclodextrin polymer and hold as much as 700 ± 150 g cm −2 .